Private Demand for Dengue Vaccine in Bangkok, Thailand - ขันคำ วันวิสาข์; คงศีล สุคนธา; เจียมตน สุขุม; ลิ่วลักษณ์ วงวัฒน์ (Journal of Health Science of Thailand, 2020)
The research was a cross-sectional survey aiming to examine private demand and associated factors for private demand on dengue vaccine. The study samples were 299 individuals who lived in Bangkok in 2017: 5 districts with highest morbidity rate and other 5 districts with lowest morbidity rate of dengue disease selected as samples which were calculated from Daniel WW formula. Systematic sampling was utilized in the recruitment process. Data were analysed using Chi-Squared, Fisher Exact, Mann-Whitney test and multiple linear regression. The results demonstrated that 57% of study population had private demand for dengue vaccine. Initial analyses showed that factors e.g. age, occupation, education level, personal and family income, household expense, pre-existing medical conditions, medical care entitlements, residential settings and willingness to pay were statistically significantly associated with private demand for dengue vaccine (p <0.05). From multiple linear regression, the final 3 predictive factors included income, age and willingness to pay were associated with private demand for dengue vaccine. These three factors showed a predictability rate of 15.9% (R2 =0.159, p=0.01). It is recommended that dengue vaccine implementation should include subsidary from the government and co-payment by the client. The campain should be focused in 9-45 age group who are primary target for dengue vaccination.